Kinetic Barrier Against Standing Up of Pentacene Molecules Upon a Pentacene Monolayer. Issue 8 (25th June 2018) - Zhang, Lei; Huo, Shuchun; Fu, Xing; Hohage, Michael; Sun, Lidong
Abstract : The growth of pentacene thin films on Cu(110)‐(2 × 1)O surface was investigated in situ and in real time using reflectance difference spectroscopy (RDS). Deposition at a substrate temperature of 230 K results in a lying‐down orientation for all pentacene molecules. Subsequent annealing to a temperature of 350 K induces reorientation for molecules above the first monolayer into a standing‐up configuration. By a quantitative analysis on the corresponding evolution of the RD signals, the kinetic barrier of 970 ± 150 meV has been deduced for the reorientation of pentacene molecule. Abstract : Pentacene deposition on Cu(110)‐(2 × 1)O surface at 230 K results in a lying‐down orientation. Subsequent annealing to 350 K induces reorientation for molecules above the first monolayer into a standing‐up configuration. By a quantitative analysis on the corresponding evolution of the optical signals, the kinetic barrier of 970 ± 150 meV has been deduced for the reorientation of pentacene molecule.